Hubungan Antara Harga Diri dengan Kesejahteraan Psikologis pada Mahasiswa di Universitas Aisyah Pringsewu - Galuh Pradnya Farmasita; Rima Wilantika (Indonesian Journal Publisher, 2023)
The research conducted by the author aims to analyze and describe the relationship between self-esteem in students and the psychological level called prosperity in students at Aisyah Pringsewu University. The population in the research carried out were students at Aisyah Pringsewu University. The research subjects were 97 students. The research was carried out using a quantitative approach system, using product moment correlation analysis techniques. Based on the coefficient of determination, the contribution of effective self-esteem to the level of psychological well-being is 41.86%. The research results obtained were that a positive relationship was found between self-esteem and psychological well-being in Aisyah Prinsewu University students (r = 0.647; p = 0.000). This represents that the higher the self-esteem of students, the higher the psychological well-being they have. This also applies vice versa, if the lower the self-esteem, the lower the psychological well-being of students at Aisyah Pringsewu University.